Sustaining the boom: the critical role of safe and sustainable technology in Bangladesh’s broiler industry (Asian-Australasian Journal of Food Safety and Security, 2025)
The broiler industry in Bangladesh has grown rapidly from small backyard farms into a major commercial sector, helping to meet the country’s growing demand for protein. However, this fast expansion has also brought challenges, including frequent disease outbreaks, rising antimicrobial resistance (AMR), and environmental impacts from intensive farming. Diseases like Avian Influenza (AI) and Newcastle Disease (ND) often lead to the overuse of antibiotics, contributing to the emergence of multidrug-resistant bacteria and antibiotic residues in poultry products, which pose risks to public health. At the same time, waste management and other environmental pressures from large-scale production add further strain. This review not only highlights these problems but also explores practical solutions. Measures such as improved biosecurity, targeted vaccination, and scientifically-supported alternatives to antibiotics—like probiotics, prebiotics, and plant-based feed additives—can help maintain productivity while reducing health and environmental risks. The approach is framed within a "One Health" perspective, recognizing the close links between animal, human, and environmental health. The future of the broiler industry in Bangladesh depends on adopting sustainable, integrated practices. This requires stronger policy enforcement, farmer education, investment in local research and development, and collaboration through public-private partnerships. By following this roadmap, stakeholders can transform the sector into a safer, more sustainable industry that protects public health, supports farmers, and ensures long-term food security. This review provides a critical evidence base and a strategic framework for policymakers, industry leaders, and researchers to collaboratively transform the Bangladeshi broiler sector into a model of sustainable and safe production.Asian Australas. J. Food Saf. Secur. 2025, 9(2), 31-46